2003
DOI: 10.1021/ie0210309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethersulfone on the Mechanical and Rheological Properties of Polyetherimide-Modified Epoxy Systems

Abstract: The reaction-induced phase separation process of polyethersulfone-and polyetherimide-modified (PES-and PEI-modified) epoxy systems was investigated by using transmission electronic microscopes (TEM) and a rheometry instrument. The morphologies of cured blends alter considerably with the PES content and molecular weight at the same content of total thermoplastics. Compared with the PEI-modified systems, many complex phase separation mechanisms are observed due to the introduction of PES, but similar relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…Oxazolidinone ring system plays a pivotal role in engineering materials due to their exceptional mechanical and thermal attributes . Several studies were also reported related to polyethersulfone (PES) toughened cured epoxy network and their toughening mechanism …”
Section: Introductionmentioning
confidence: 99%
“…Oxazolidinone ring system plays a pivotal role in engineering materials due to their exceptional mechanical and thermal attributes . Several studies were also reported related to polyethersulfone (PES) toughened cured epoxy network and their toughening mechanism …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several investigations were conducted on the successful improvement of epoxy resin mechanical properties by using layered nanoclays [5,[9][10][11][12] or thermoplastics modifiers [13][14][15][16][17][18]. In recent years, layered nanoclays such as montmorillonite were also combined with thermoplastics such as poly(methyl methacrylate) (PMMA) to enhance the properties of epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, much work has been made to toughen highly crosslinked thermosetting polymers with high modulus, high glass transition temperature thermoplastics, such as polyethersulfone (PES) [1,2] , polysulfone (PSF) [3] , poly (ether ether ketone) (PEEK) [4] and polyetherimide (PEI) [5,6] . Since the mechanical properties of the materials are determined by their final morphologies, much work has been focused on mechanism study of phase separation and morphology control [7][8][9][10][11][12][13] . Effective improvement in toughness can only be obtained at high fractions of the engineering thermoplastic [14,15] , where the thermoplastic forms a continuous phase with the epoxy spherical domain, or the thermoplastic and epoxy form a bicontinuous phase structure.…”
Section: Introductionmentioning
confidence: 99%